The Obligation of Pasar Pitu Tradition on Pre-Marriage implementation in Maqosid Shari'ah Analysis - Widiyanto, Hari; Khasanah, Fitrohtul; Saifudin, Saifudin; Nursobah, Achmad; Malikhah, Wafiyatul (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
The relationship between Islamic law and the pitu market tradition in the form of practices carried out by Javanese society as part of pre-marriage is a form of strengthening in the development of Islamic law and gluing together traditions that develop in the community, so that this tradition is based on the maqosid sharia approach by involving prospective brides that visit seven different markets before getting married needs to be tested for its relationship and contribution to Islamic law and the community tradition. The research method used in the study used a qualitative study by conducting in-depth interviews with analysis using maqosid sharia. This research shows that the pitu market tradition has values in line with several fundamental aspects in the maqosid sharia framework such as hifz al-din and hifz al-'aql, hifz al-nasl, hifz al-mal. Thus the market pitu tradition carried out by the community as a pre-marriage has social, spiritual, and economic values in running the bride and groom's household life in the future. This market pitu tradition is a practice that is believed to provide blessings and introduce a form of responsibility if after a marriage from various aspects in the practice of the market pitu tradition.